A "country" rich in needs: an experiment in Seminario en Enfermeria of Salud Publica (1962) - Petite Fleur Custódio da Silva; Aline Dos Santos da Silva; Erika Bicalho de Almeida; Julieta Brites Figueiredo; Vanessa Costa Cavalcanti; Wellington Mendonça Amorin (Universidad de Alicante, 2018)
The study aimed to discuss the intended effects on Latin American nurses legitimated by the fictional strategy for the planning of public health nursing. Qualitative research approach based on the historical perspective of the Cultural History of the French historian Roger Chartier, and operationalized in the technical documentation of observation, and as a source publication Tell Del Seminario of Public Health - PAHO categories emerged after analyzing needs, planning and fictional narrative health actions. Result: he met through the fictional narrative power relations, social configurations of class and character and context of nurses in Latin America. It is concluded that the strategy of the seminar enabled the construction of collective and joint proposals from the exchange of experiences between the participating nurses.